2008
DOI: 10.1002/ejoc.200700902
|View full text |Cite
|
Sign up to set email alerts
|

2,6‐Disubstituted Tetrahydropyrans by Tandem Cross‐Metathesis/Iodocyclisation

Abstract: A new approach to 2,6-disubstituted tetrahydropyrans by a tandem cross-metathesis/iodocyclisation reaction has been developed. The stereochemical outcome of the cyclisation reactions has been studied for different substrates. This sequence has allowed the preparation of a series of cis-and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Interested by all the concepts which allow the development of green organic chemistry, we especially turn our attention to sequential reactions which avoid intermediate purifications. 17,18 One of the major problems to overcome is the choice of the solvent, which has to be efficient in different reactions, solventless conditions being the ideal case. There are only a few examples of solvent-free Prins reaction in the literature: Borah et al used the SiO 2 p-TSA catalyst under solventless microwave irradiation conditions for the synthesis of 1,3-dioxanes 19 and Dos Santos et al reported the use of the same catalyst for the synthesis of THP odorants.…”
mentioning
confidence: 99%
“…Interested by all the concepts which allow the development of green organic chemistry, we especially turn our attention to sequential reactions which avoid intermediate purifications. 17,18 One of the major problems to overcome is the choice of the solvent, which has to be efficient in different reactions, solventless conditions being the ideal case. There are only a few examples of solvent-free Prins reaction in the literature: Borah et al used the SiO 2 p-TSA catalyst under solventless microwave irradiation conditions for the synthesis of 1,3-dioxanes 19 and Dos Santos et al reported the use of the same catalyst for the synthesis of THP odorants.…”
mentioning
confidence: 99%
“…2 Owing to the importance of chiral tetrahydropyran structures, which are characteristic structural features of many natural products, these heterocycles have attracted considerable attention in recent years and many methods have been developed for the preparation of this framework. 3,4 Recently we and others reported that chromanols 6 can be efficiently synthesized through a Michael addition of 1,3-dicarbonyl compounds 1 to nitrovinylphenol 5 and subsequent intramolecular hemiacetalization. 5 The hydroxyl group participates in this process through carbonyl addition and makes this sequence a powerful tool among the existing annulation methods (Scheme 1, a).…”
mentioning
confidence: 99%
“…We now would like to report an efficient organocatalytic asymmetric synthesis of functionalized tetrahydropyranols 3 by hydrogen bonding activation of α-hydroxymethyl nitroalkenes 2 as Michael acceptors via a domino Michael–hemiacetalization reaction followed by dehydration to form dihydropyrans 4 (Scheme 1, b). 4b,h-j,6…”
mentioning
confidence: 99%
“…8 b-hydroxy ester 11, acid 12 was readily available (85%, Scheme 5). However, allylic oxidation to furnish lactone 13 failed.…”
mentioning
confidence: 99%